Changes in type 2 diabetes incidence and mortality associated with introduction of HbA1c as diagnostic option: A Danish 24-year population-based study - Jakob S. Knudsen; Signe Schöllhammer Knudsen; Ádám Hulmán; Daniel R. Witte; Edward W. Gregg; Torsten Lauritzen; Lars Pedersen; Henrik Toft Sørensen; Reimar W. Thomsen (2022)
Background: In 2011, the World Health Organization began recommending glycated haemoglobin (HbA1c) as a measure for diagnosing type 2 diabetes (T2D). This initiative may have changed basic T2D epidemiology. Consequently, we examined time changes in T2D incidence and mortality during 1995-2018. Methods: In this population-based cohort study, we included 415,553 individuals with incident T2D. We calculated annual age-standardized incidence rates of T2D. We examined HbA1c testing and used Poisson-regression to investigate all-cause mortality among the T2D patients and a matched comparison cohort from the general population over successive 3-year periods. Findings: From 1995 to the 2012 introduction of HbA1c testing as a diagnostic option in Denmark, the annual standardized incidence rate (SIR) of T2D doubled, from 193 to 396 per 100,000 persons (4.1% increase annually). From 2012 onwards, the T2D incidence declined by 36%, reaching 253 per 100,000 persons in 2018 (5.7% decrease annually). This was driven by fewer patients starting treatment with an HbA1c measurement of <6·5% or without prior HbA1c testing. Mortality per 1,000 person-years following a T2D diagnosis decreased by 44% between 1995-1997 and 2010-2012, from 69 deaths to 38 deaths (adjusted mortality rate ratio: 0·55 (95% CI: 0·54-0·56)). After the low level during 2010-2012, mortality increased again by 27% to 48 per 1,000 person-years (95% CI: 46-50) by 2016-2018. Interpretation: Our findings suggest that introducing HbA1c as a diagnostic option may have changed basic T2D epidemiology by leaving patients undiagnosed, that previously would have been diagnosed and treated. Funding: Aarhus University funded the study and had no further involvement.